The functional role of the pulvinar in discriminating between objective and subjective cognitive impairment in major depressive disorder - Yuluğ, Burak; Ayyıldız, Sevilay; Sayman, Dila; Karaca, Ramazan; İpek, Lütfiye; Çankaya, Şeyda; Salar, Ali Behram; Ayyıldız, Behçet; Mikuta, Christian; Yağcı, Nilay; Özdemir Öktem, Ece; Özşimşek, Ahmet; et al. (John Wiley and Sons Inc, 2024)
INTRODUCTIONEmotionally driven cognitive complaints represent a major diagnostic challenge for clinicians and indicate the importance of objective confirmation of the accuracy of depressive patients' descriptions of their cognitive symptoms.METHODSWe compared cognitive status and structural and functional brain connectivity changes in the pulvinar and hippocampus between patients with total depression and healthy controls. The depressive group was also classified as "amnestic" or "nonamnestic," based on the members' subjective reports concerning their forgetfulness. We then sought to determine whether these patients would differ in terms of objective neuroimaging and cognitive findings.RESULTSThe right pulvinar exhibited altered connectivity in individuals with depression with objective cognitive impairment, a finding which was not apparent in depressive patients with subjective cognitive impairment.DISCUSSIONThe pulvinar may play a role in depression-related cognitive impairments. Connectivity network changes may differ between objective and subjective cognitive impairment in depression and may play a role in the increased risk of dementia in patients with depression.
Keywords: Amnestic Depression; Cognition; Depression; Functional Magnetic Resonance Imaging; Pulvinar